The genus Contracaecum Raillet & Henry (Nematoda: Anisakidae): host and geographical distribution on Neotropical and Antarctic species - Garbin, Lucas E.; Diaz, Julia I.; Servián, Andrea; Fusaro, Bruno; Navone, Graciela T. (Zenodo, 2023)
Garbin, Lucas E., Diaz, Julia I., Servián, Andrea, Fusaro, Bruno, Navone, Graciela T. (2023): The genus Contracaecum Raillet & Henry (Nematoda: Anisakidae): host and geographical distribution on Neotropical and Antarctic species. Zootaxa 5256 (1): 43-62, DOI:10.11646/zootaxa.5256.1.3, URL: http://dx.doi.org/10.11646/zootaxa.5256.1.3